Kiss the blood off my hands : on classic film noir - Miklitsch, Robert, 1953- (University of Illinois Press, 2014)
Consider the usual view of film noir: endless rainy nights populated by down-at-the-heel boxers, writers, and private eyes stumbling toward inescapable doom while stalked by crooked cops and cheating wives in a neon-lit urban jungle. But a new generation of writers is pushing aside the fog of cigarette smoke surrounding classic noir scholarship. In Kiss the Blood Off My Hands: On Classic Film Noir, Robert Miklitsch curates a bold collection of essays that reassesses the genre's iconic style, history, and themes. Contributors analyze the oft-overlooked female detective and little-examined aspects of filmmaking like love songs and radio aesthetics, discuss the significance of the producer and women's pulp fiction, as well as investigate Disney noir and the Fifties heist film, B-movie back projection and blacklisted British directors. At the same time the writers' collective reconsideration unwinds the impact of hot-button topics like race and gender, history and sexuality, technology and transnationality. As bracing as a stiff drink, Kiss the Blood Off My Hands writes the future of noir scholarship in lipstick and chalk lines for film fans and scholars alike.